Antineoplastic Activity of New Transition Metal Complexes of 6-Methylpyridine-2-carbaldehyde-N(4)-ethylthiosemicarbazone: X-Ray Crystal Structures of [VO2(mpETSC)] and [Pt(mpETSC)Cl] - Shadia A. Elsayed; Ahmed M. El-Hendawy; Sahar I. Mostafa; Bertrand J. Jean-Claude; Margarita Todorova; Ian S. Butler (Bioinorganic Chemistry and Applications)
New complexes of dioxovanadium(V), zinc(II), ruthenium(II), palladium(II), and platinum(II) with 6-methylpyridine-2-carbaldehyde-N(4)-ethylthiosemicarbazone (HmpETSC) have been synthesized. The composition of these complexes is discussed on the basis of elemental analyses, IR, Raman, NMR (H1, C13, and P31), and electronic spectral data. The X-ray crystal structures of [VO2(mpETSC)] and [Pt(mpETSC)Cl] are also reported. The HmpETSC and its [Zn(HmpETSC)Cl2] and [Pd(mpETSC)Cl] complexes exhibit antineoplastic activity against colon cancer human cell lines (HCT 116).